2001
DOI: 10.3168/jds.s0022-0302(01)70179-8
|View full text |Cite
|
Sign up to set email alerts
|

Site of Nutrient Digestion by Dairy Cows Fed Corn of Different Particle Sizes or Steam-Rolled

Abstract: Five primiparous Holstein cows were cannulated in the rumen, duodenum, and ileum and were fed diets containing 50% alfalfa silage and 36.6% coarse-, medium-, or fine-ground corn (CGC, MGC, and FGC, respectively, with mean particle sizes of 4.8, 2.6, or 1.2 mm), steam-rolled corn (SRC; density of 0.53 kg/L), or a 50:50 mix of CGC and SRC (SC) to evaluate how corn processing affects site of digestibility of nonstructural carbohydrates (NSC) and neutral detergent fiber (NDF). Decreasing the particle size of corn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
4
10

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 37 publications
10
66
4
10
Order By: Relevance
“…Outros pesquisadores (San Emeterio et al, 2000;Soriano et al, 2000;Callison et al, 2001;Reis et al, 2001) também não observaram efeitos de diferentes formas de processamento de milho sobre o teor de gordura do leite.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Outros pesquisadores (San Emeterio et al, 2000;Soriano et al, 2000;Callison et al, 2001;Reis et al, 2001) também não observaram efeitos de diferentes formas de processamento de milho sobre o teor de gordura do leite.…”
Section: Resultsunclassified
“…Não houve efeito das dietas sobre o teor de proteína do leite (P>0,05), semelhantemente ao observado por San Emeterio et al (2000), Soriano et al (2000), Reis et al (2001) e Callison et al (2001). Com os efeitos benéficos da associação de milho de maior degradabilidade com casca de soja e de milho de menor degradabilidade com a polpa cítrica, conforme discutido anteriormente, houve tendência (P<0,06) de interação grau de moagem × subproduto para produção de proteína do leite.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…10) by corn processing. Previous studies showed no differences in DMI or milk production when compared to coarse-ground and finely ground corn (Callison et al, 2001, RBmond et al, 2004. On the other hand, some studies (Harvantine et al, 2002) observed a decrease in DMI when SFC corn replaced DR corn in diet.…”
Section: Dr-mg and Dr-cg)mentioning
confidence: 95%
“…Nossos resultados são similares descritos por Oba e Allen (2003c) os quais em estudo comparando dietas com silagem de grão úmido e milho moído seco em dois níveis de amido na dieta não observaram efeito sobre a digestibilidade da fibra dietética. Resultados de estudos sobre DFDN e aumento da degradabilidade de amido são variáveis (CALLISON et al, 2001). Até mesmo correlações positivas entre digestibilidade do amido e da fibra tem sido relatadas (TAYLOR; ALLEN, 2005).…”
Section: Resultsunclassified